CALCIUM STATUS IN PREMENOPAUSAL AND POSTMENOPAUSAL WOMEN - Qureshi, Hamid Javaid; Hussain, Ghulam; Jafary, Zafar Altaf; Bashir, Muhammad Usman; Latif, Naghmana; Riaz, Zeeshan (Journal of Ayub Medical College Abbottabad, 2010)
Background: In postmenopausal women, the two major causes of bone loss are oestrogen deficiency after menopause and age related processes. Bone turnover increases to high levels and oestrogen deficiency may induce calcium loss by indirect effects on extra skeletal calcium homeostasis. Objective of this study was to evaluate calcium status in pre-menopausal and postmenopausal women. Methods: This cross sectional study was carried out in 34 premenopausal women and 33 postmenopausal women, in Department of Physiology, Services Institute of Medical Sciences, Lahore. Height and weight of each woman were taken to find out the body mass index (BMI). Serum calcium, parathyroid hormone and calcitonin levels of each subject were determined. Results: Premenopausal women were obese (BMI>30 Kg/m2) while postmenopausal women were overweight (BMI>25 Kg/m2). Serum calcium levels were significantly lower in postmenopausal women than in pre-menopausal women, while serum parathyroid hormone levels were significantly higher in postmenopausal woman. Serum calcitonin level was not significantly different in the two groups. Conclusion: Postmenopausal women are calcium deficient and have increased bone turnover as indicated by increased serum parathyroid hormone levels. Keywords: Premenopausal, postmenopausal, calcium, parathyroid hormone, calcitonin.